Crescimento inicial e nutrição de cedro (Cedrela fissilis Vell.) em função de doses de nitrogênio - Freiberger, Mariângela Brito [UNESP]; Guerrini, Iraê Amaral [UNESP]; Galetti, Gabriela; Fernandes, Dirceu Maximino [UNESP]; Corrêa, Juliano Corulli (FapUNIFESP (SciELO), 2013)
We aimed to evaluate the effects of nitrogen rates in early growth, SPAD index, content and accumulation of nutrients in cedar seedlings. The experiment was carried out in a plastic greenhouse and the seedlings were grown in plastic pots filled with 20 dm-3of Rhodic Hapludox, arranged inrandomized blocks with four replications. Rates of 0, 40, 80, 120 and 160 mg dm-3N were tested. Fertilization up to 160 mg dm-3N promoted increases in SPAD index and early growth of plants, beyond greater absorption of N,P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn. Overall, lower N rates limited growth but not the absorption of nutrients by cedar plants. In leaves, the only nutrien taffected was the B which their content was reduced with increasing of N rate. Increased of nitrogen fertilization changed the Cu distributionin plants, since increased Cu content in roots and reduced their content in stem. Higher N rates promoted higher accumulation of all nutrients due to the increase of dry matter. Nitrogen fertilization changed the dynamic of nutrient absorption in cedar. With 160 mg dm-3N, the amount absorbed followed the order: N>S>Ca>K>Mg>P>Fe>Mn>B> Zn> Cu.
Early growth and nutrition of cedar (Cedrela fissilis Vell.) as affected by nitrogen rates
Keywords: Content and accumulation; Macronutrient and micronutrient; SPAD index